2000
DOI: 10.1097/00019606-200009000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study for Identifying Promoter Allelic Polymorphism in Interleukin 10 and Tumor Necrosis Factor α Genes

Abstract: Cytokines such as tumor necrosis factor (TNF)-alpha and Interleukin (IL)-10 play significant roles in autoimmunity and transplantation tolerance. Allelic polymorphisms that occur in the regulatory regions of these cytokine genes are closely associated with acute and chronic transplant rejection. The presence of a G-to-A polymorphism at position -308 in the promoter region of the TNF-alpha gene can increase transcription six- to sevenfold. Likewise, the G-A polymorphism at position -1082 of the IL-10 promoter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…18,19 The presence of a G to A polymorphism at position 308 of the TNF a promoter gene could increase transcription six-to seven-fold. 20 It is obvious that the variable polymorphisms that lie within the promoter region of the TNF a locus make it a likely candidate for playing a regulatory role in disease. In our study, owing to the frequency of the À308A allele noted in POAG patients, we have to consider the possibility that a functional distinction between A…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The presence of a G to A polymorphism at position 308 of the TNF a promoter gene could increase transcription six-to seven-fold. 20 It is obvious that the variable polymorphisms that lie within the promoter region of the TNF a locus make it a likely candidate for playing a regulatory role in disease. In our study, owing to the frequency of the À308A allele noted in POAG patients, we have to consider the possibility that a functional distinction between A…”
Section: Discussionmentioning
confidence: 99%
“…Agarwal et al (50) found that a G-to-A polymorphism at position Ϫ308 in the promoter region of the TNF-␣ gene increases transcription up to sevenfold and that the G-to-A polymorphism at position Ϫ1082 of the IL-10 promoter results in lower levels of IL-10 protein.…”
Section: Discussionmentioning
confidence: 99%
“…24 The presence of a G to A polymorphism at position 308 of the TNF-a promoter gene could increase transcription six-to seven-fold. 25 The IL-1b gene is located on chromosome 2, in close linkage with another gene of the IL-1 gene family that encodes for IL-1Ra. Different polymorphisms have been described in the IL-1b gene and at least two of them could influence the protein production: one located in the promoter region at position À511, 19 and the other in exon 5.…”
Section: Discussionmentioning
confidence: 99%